Homeostasis of intestinal immune regulation. - Annacker, O; Powrie, F (2002)
Regulatory CD4 T cells with the capacity to inhibit potentially harmful immune responses have been described in various experimental systems. Although the observations are converging towards the naturally activated CD25(+) CD4 T cells as a major population responsible for this protection, there is still considerable disagreement on the molecular and cellular requirements involved to achieve a stable immune homeostasis in vivo.